Exploring the psychometric properties of the Persian Depression Anxiety Stress Scale for Youth (DASS-Y): factor structure and reliability in Iranian children and adolescents - Shabani, Mohammad Javad; Gharraee, Banafsheh; Zahedi Tajrishi, Komeil (Frontiers in Psychology, 2025)
BackgroundThe Depression Anxiety Stress Scale for Youth (DASS-Y) is a self-report instrument recently developed to evaluate negative emotional states in children and adolescents. However, the Persian version’s factor structure and psychometric properties have yet to be investigated in Iranian youth. The study aimed to assess the factor structure and reliability of the Persian DASS-Y in a sample of Iranian children and adolescents.MethodsThe study recruited 1,277 children and adolescents, 703 (55.1%) being girls and 574 (44.9%) being boys (aged 7–18 years), from schools in Tehran, Iran. Confirmatory factor analysis (CFA) was conducted to evaluate structural validity and test the fit of three-factor models. Internal consistency reliability was examined using Cronbach’s alpha and McDonald’s omega coefficients for the DASS-Y total and subscale items. Convergent and discriminant validity were also assessed.ResultsThe CFA results supported the original 3-factor structure of the DASS-Y, consisting of Depression, Anxiety, and Stress subscales in both groups of Iranian children and adolescents. Subsequently, the Pearson correlation coefficient assessed the scale’s convergent and discriminant validity, which was relatively appropriate. Also, the DASS-Y’s internal consistency reliability was satisfactory.ConclusionThe Persian DASS-Y is a reliable and valid Instrument for measuring depression, anxiety, and stress in Iranian children and adolescents. It can be helpful for both research and clinical work, helping to assess psychological distress in children and adolescents.